Writing Errors Hiragana and Katakana In PGSD, PTIK, and PBI IPB Cirebon Study Programs - Maulina Prastika, Tiara; Kristianto Gunawan, Theodore; Hidayati, Yanti (Green Publisher Indonesia, 2023)
The research aims to describe hiragana and katakana letter writing errors made by students of PGSD, PTIK, and PBI study programs of Invada Institute of Education and Language and describe the causes of letter writing errors made by these students. The sources of data used are essay writing or sakubun about students' daily activities based on the Marugoto A1 book and questionnaires. The method used is descriptive qualitative and uses a questionnaire to find out the causes of errors in writing the letters. The results of this study show that there are 35 data of correspondent name writing errors, both mixed writing and errors on several letters, 40 data of time writing errors, 73 data in the form of place writing errors, and 20 data of writing errors on activities or daily activities. The factors underlying the letter writing errors are the lack of memorization, writing, and not re-reading the material given and the difficulty when memorizing the letters hiragana and katakana